The place kick in rugby - Padulo, J.; Granatelli, G.; Ruscello, B.; D`Ottavio, S. (The Journal of Sports Medicine and Physical Fitness, 2013)
Aim: The paper aims at studying the technical place kick in rugby, frontally to the try and at 40 meter distance. The relationship between the type of run with a predefined number of holds (1 to 4), the kinematics variables (the angle variation of the lower limbs, at the time of loading and at the moment of the impact against the ball), the average ball movement speed were assessed. Methods: Six men national athletes, took part in the study. All the kicks were video-recorded with two high speed (210 Hz) digital cameras, and processed with Dartfish 5.5Pro software. Results: According to the type of run, significant differences were reported on the run time (PConclusion: The analysis of the different types of runs lead to the definition of the best possible conditions for such a specific sport move, to be suggested during application or training for specialised athletes.